Actitudes del consumidor después de elegir un producto equivocado (2011)
Because of consumers' confusion with an over the counter drug, feelings of frustration lead an individual to particular behavioral intentions. Consumers' attitude towards confusion is the relationship between their emotions and behavioral intentions (i.e., changing the product, intention to seek for information, and intention to consume). This relationship is analyzed in an experimental setting simulating a wrong decision. Results demonstrate that a) emotions due to confusion explain higher intentions to exchange a product and that b) this is then associated with lower intentions of taking a medicine and higher intentions of gathering information.